Evaluation as Part of Operations: Reconciling the Common Rule and Continuous Improvement - Platt, Richard (The Hastings Center report, 2013)
Understanding the components of clinical care that work best is a cornerstone of improving health care. And yet, the more we improve the quality of quality improvement and move to continuous learning about clinical care more broadly, the more we find ourselves in a regulatory environment that makes evaluation more difficult, expensive, and, in some situations, impossible. In their paper on the ethical underpinnings of the distinction between research and treatment, Ruth Faden and colleagues raise important implications for a wide array of situations. These points give reason to rethink the definition of routine clinical operations to include evaluation of the processes and outcomes of care and dissemination of findings. We concur with the assertion by Faden and colleagues, and with previous work from The Hastings Center, that conducting continuous improvement activities such as these is an obligation of health systems and clinicians. We believe that rigorous, systematic evaluation should be considered part of normal, expected operations, rather than exceptional behavior that requires extraordinary regulatory control.